Anxiety Score as a Risk Factor for Radial Artery Vasospasm During Radial Interventions: A Pilot Study. (January 2014) - Ercan, Suleyman; Unal, Ahmet; Altunbas, Gokhan; Kaya, Hilal; Davutoglu, Vedat; Yuce, Murat; Ozer, Orhan
We determined the role of anxiety level on radial artery spasm during transradial coronary angiography. Eighty-one patients who had an indication for coronary angiography were enrolled. Radial artery vasospasm was determined by addressing 5 signs: persistent forearm pain, pain response to catheter manipulation, pain response to sheath withdrawal, difficult catheter manipulation after being "trapped" by the radial artery, and considerable resistance on withdrawal of sheath. Radial spasm defined as at least 2 of the 5 signs. The Hamilton Anxiety scale questionnaire was used to determine the level of anxiety. Vasospasm was observed in 19.1% of the patients. Anxiety score was significantly higher in women (11.1 ± 7.2 vs 17.6 ± 7.3; P < .001). Vasospasm was significantly correlated with female sex ( P < .001, r = .43) and anxiety score ( P = .007, r = .29). Female sex was associated with higher anxiety scores ( P < .001, r = .43). In conclusion, higher anxiety scores and female sex are important risk factors for radial artery vasospasm.